Understanding Wisconsin Legislators' Use of Social Media - (:unkn) unknown (My University, 2013)
This thesis used quantitative and qualitative methods to examine the use of social media by legislative offices of the Wisconsin State Assembly. A survey of legislators and their staff documented the extent to which each office uses Facebook or Twitter. In addition, multivariate analysis of the survey data provided an understanding of which kinds of legislators are more likely to use Facebook or Twitter. There were three important findings. First, most Wisconsin legislators whose offices use Facebook or Twitter do not seem to be doing so to reach the news media. Second, overall, the characteristics of a Wisconsin legislator are stronger predictors on the use of Facebook or Twitter by a legislative office than the characteristics of a legislator's district. Third, constituent access to broadband is a significant predictor of whether a legislative office in the Wisconsin State Assembly uses Facebook.
Keywords: Facebook; Legislative Social Media Use; Social Media; Twitter; Wisconsin Legislature